Observation of Phase Transformations in High-temperature Chamber under Microscope Objective Lens - Pekovic, Michal; Opatova, Katerina; Rubesova, Katerina; Janda, Tomas; Jirkova, Hana; Bures, Radovan (Manufacturing Technology Journal, 2019)
Today, extensive information on a particular material can be obtained from its chemical composition using various computer programs. Such information includes phase transformation temperatures, such as Ac1 and Ac3 or the Ms and Mf, as well as the entire austenite decomposition sequence, as shown in TTT and CCT diagrams. When steel is heated, austenite grains begin to form, grow and eventually coarsen. On cooling, these grains decompose into pearlite, ferrite, cementite and hardening phases. Transformations of this kind are well understood nowadays, namely the ways the individual phases form and the rates and temperatures involved. Yet, in-situ visual recordings of such transformations are relatively rare. Using the Linkam TS1400XY heating stage, which is capable to heat samples up to 1400°C and is integrated in an optical microscope featuring objective lenses with modified working distances, these phase transformations can be observed directly. This paper explores the potential of the heating stage for studying various materials and their specific heat treatments. It also discusses the method of sample preparation for use in the heating stage placed in an optical microscope.
Keywords: heating stage; phase transformations; optical microscopy; heat treatment